Women's views and preferences regarding the mode of birth after cesarean section: Polish cross-sectional web-based survey. (June 2022) - Sys, Dorota; Baranowska, Barbara; Kajdy, Anna; Tataj-Puzyna, Urszula; Gotlib, Joanna; Bączek, Grażyna; Juszczakiewicz, Paulina; Rabijewski, Michał
Abstract: Objective: Currently, the most common indication for cesarean section is a previous cesarean section. Some of them are performed for no medical reasons. Therefore, it is crucial to recognize the preferences and expectations of women concerning birth after cesarean section. This study's main aim was to understand the women's points of view on the mode of birth after cesarean. Study design: A cross-sectional study was conducted, and data was collected using an original structured online questionnaire. The study group consisted of 733 pregnant Polish women who had previously undergone a cesarean birth. Results: Women more often preferred vaginal birth after cesarean section (73.26%) and less frequently (23.33%) chose elective cesarean section. Women preferring VBAC when making decisions were guided by the benefits, opportunities, and risks associated with each mode of birth. For women preferring elective cesarean section the only highly significant factor was the experience of previous deliveries. Women mainly use Internet sources and the support of other women giving birth after cesarean section. More than half of the women did not talk about the mode of birth with their midwife, and every fifth did not talk about it with the obstetrician. Conclusion: Obstetric history and personal beliefs about birth after cesarean section, motivations, and concerns about childbirth affect women's preferences regarding the mode of birth. It is necessary to educate women, in particular, talks about the opportunities and risks associated with cesarean birth carried out by the medical staff at an early stage of pregnancy.